Roman law - a unique phenomenon of legal culture - Колодій, Анатолій Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Scientific review of the textbook for universities of R. A. Kalyuzhnyy, V. M. Volk "Roman private law".